(untitled) (2010)
Analytical and experimental research for determining the seismic vulnerability of ferrocement houses, which is a low-cost system using precast thin panels, is presented. The research comprises the following tasks: (a) a field survey on the ferrocement dwelling houses actually built in seismic regions in Colombia; (b) a cyclic load test on 1:1 scale models; (c) identification of the parameters of the Bouc-Wen hysteretic model for the observed panel behaviour; and (d) Monte Carlo simulations of models intended to estimate the fragility curves of the houses. Despite the models exhibiting stiffness degradation, it was concluded that the system is adequate for regions of moderate to high seismicity. © 2010 Taylor & Francis.